A new approach to improve the electrochemical performance of ZnMn2O4 through a charge compensation mechanism using the substitution of Al3+ for Zn2+. Issue 14 (15th February 2018) - Zhu, Xianyu; Quan, Jingbin; Huang, Jichun; Ma, Zheng; Chen, Yixin; Zhu, Decheng; Ji, Chongxing; Li, Decheng
Abstract : This work reports the nonequivalent substitution of ZnMn2 O4 . This is a new approach to improve the electrochemical performance of ZnMn2 O4 through a charge compensation mechanism using the substitution of Al 3+ for Zn 2+ . Abstract : ZnMn2 O4 and Zn1− x Al x Mn2 O4 were synthesized by a spray drying process followed by an annealing treatment. Their structural and electrochemical characteristics were investigated by SEM, XRD, XPS, charge–discharge tests and EIS. XPS data indicate that the substitution of Al 3+ for Zn 2+ causes manganese to be in a mixed valence state by a charge compensation mechanism. Moreover, the presence of this charge compensation significantly improves the electrochemical performance of Zn1− x Al x Mn2 O4, such as increasing the initial coulombic efficiency, stabilizing the cycleability as well as improving the rate capability. The sample with 2% Al doping shows the best performance, with a first cycle coulombic efficiency of 69.6% and a reversible capacity of 597.7 mA h g −1 after 100 cycles. Even at the high current density of 1600 mA g −1, it still retained a capacity of 558 mA h g −1 .